2020
DOI: 10.3389/fnins.2020.602235
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Adsorbs to Polypropylene Tubes and Disrupts Functional Assays: Implications for Research, Biomarker Studies, and Therapeutics

Abstract: Progranulin (PGRN) is a tightly regulated, secreted glycoprotein involved in a wide range of biological processes that is of tremendous interest to the scientific community due to its involvement in neoplastic, neurodevelopmental, and neurodegenerative diseases. In particular, progranulin haploinsufficiency leads to frontotemporal dementia. While performing experiments with a HIS-tagged recombinant human (rh) PGRN protein, we observed a measurable depletion of protein from solution due to its adsorption onto p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…With many of the subpopulations of blood cells producing different expression levels of genes or soluble factors, these analyses in blood provide an averaged data point, losing the cell-type specific resolution of the obtained data. This may partly explain why there is no established diagnostic biomarker for ALS (yet) by using single factor analyses, in addition to the other possible explanations including technology used [ 63 ], sample sizes, co-morbidities, (anti-inflammatory) medications, and disease state at biosample donation [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…With many of the subpopulations of blood cells producing different expression levels of genes or soluble factors, these analyses in blood provide an averaged data point, losing the cell-type specific resolution of the obtained data. This may partly explain why there is no established diagnostic biomarker for ALS (yet) by using single factor analyses, in addition to the other possible explanations including technology used [ 63 ], sample sizes, co-morbidities, (anti-inflammatory) medications, and disease state at biosample donation [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…NaCl from Fisher Scientific, all other components from MilliporeSigma) supplemented with 4% bovine serum albumin (BSA, MilliporeSigma). Dilutions were made in low protein-binding tubes (ThermoFisher) to prevent progranulin from binding to the tubes ( Gururaj et al, 2020 ), and post-experimental analysis revealed no detectable loss of progranulin due to non-specific binding to tubes. Progranulin concentrations for in vitro microdialysis were 1, 2, and 5 ng/mL, which approximates the range of concentrations reported in human cerebrospinal fluid ( Batzu et al, 2020 ; Berghoff et al, 2016 ; De Riz et al, 2010 ; Meeter et al, 2016 ; Morenas-Rodriguez et al, 2016 ; Nicholson et al, 2014 ; Van Damme et al, 2008 ; Wilke et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Microdialysis sampling was conducting using an Atmos (Amuza) protein microdialysis system, consisting of a syringe pump (Amuza #ESP-180LD) to push dialysate through the probe, a peristaltic pump (Amuza #ERP-10) to pull dialysate from the probe, and a refrigerated fraction collector (Amuza #FC-90) for sample collection. Probes were perfused with aCSF supplemented with 4% BSA (MilliporeSigma) to maintain osmotic pressure ( Trickler and Miller, 2003 ) and prevent progranulin from binding to the tubing ( Gururaj et al, 2020 ). Each concentration of progranulin was measured with two one-hour samples at a flow rate of 1 μL/min, with a two-hour equilibration phase allowed when switching to each new concentration.…”
Section: Methodsmentioning
confidence: 99%